Bond and re‐anchoring tests of post‐tensioned steel tendon in case of strand failure inside cement grouting with voids. (10th April 2021) - Asp, Olli; Tulonen, Joonas; Kuusisto, Lauri; Laaksonen, Anssi
Abstract: Grouted tendons are commonly used in construction of bridges and other post‐tensioned structures. The quality of grouting is essential to provide the durability and robustness of the structure. In this paper, the bond and re‐anchoring of post‐tensioned tendons in grout in case of tendon failure is assessed. A set of tests were conducted to simulate the failure of a post‐tensioned tendon in the beam. The results were compared with the theory of prestressing strand anchoring in concrete. In the tests, the re‐anchoring and bond lengths were measured in case of complete grout and incomplete grout with void. In the case of incomplete grout, the increase in re‐anchoring length is observed. In the case of overlapping re‐anchoring and bond length, the bond length and tendon slip increase significantly. A limited re‐anchoring length of tendon in incomplete grout increases the robustness of the structure, as the broken tendon can maintain its effectiveness outside of the failure region. The existing calculation model shows a good match with test results, and therefore it is suitable for the analysis of structures with broken tendons.